Green synthesis of iron oxide nanoparticles by Taguchi design of experiment method for effective adsorption of methylene blue and methyl orange from textile wastewater - Chijioke Alex Mbachu; Akinpelu Kamoru Babayemi; Titus Chinedu Egbosiuba; John Ifeanyichukwu Ike; Ijeoma Jacinta Ani; Saheed Mustapha (Results in Engineering, 2023)
Since the beginning of the industrial revolution, the uncontrolled discharge of wastewater from textile and dyeing industries into water bodies is environmentally challenging to humans and the ecosystem. Using Cola nitida (CN) leaves extract, Taguchi optimization method was successfully applied to achieve the green synthesis of iron oxide nanoparticles (CN–Fe2O3NPs). Textural properties, nature of surface functional groups, crystalline structure and surface morphology of CN–Fe2O3NPs were studied. The performance of CN–Fe2O3NPs was tested for methylene blue (MB) and methyl orange (MO) removal from textile wastewater. The optimal surface area of 125.31 m2/g was achieved for the CN–Fe2O3NPs using the CN extract volume (10 mL), precursor concentration (2 M), contact time (30 min) and calcination temperature (600 °C). Overall, calcination temperature had the highest effect than other synthesis parameters. The characterization revealed the presence of crystalline hematite with Fe–O, Fe–O–Fe functional groups and a regular-shaped porous material. Furthermore, the adsorption capacity of 530.406 and 527.835 mg/g was obtained for MB and MO within 60 min using a nanoadsorbent dosage (25 mg/L), initial dye concentration (100 mg/L) and temperature (50 °C). The reusability and stability of the CN–Fe2O3NPs revealed successful reuse after six cycles without any damage to the structure as was corroborated by the fourier transform infrared (FTIR) spectroscopy. The experimental data were suitably fitted by the Langmuir isotherm and pseudo-second-order kinetic models denoting a chemisorption and monolayer nature of the adsorption process. The thermodynamic parameters indicate an endothermic and spontaneous adsorption process. Hence, the high separation effectiveness against the dye molecules with good performance and stability indicate the great potential for the green synthesized CN–Fe2O3NPs in water purification.